Living Experiences of Nursing Students in Caring for Covid-19 patients: a Phenomenological Study - Narges Rahmani; Majedeh Nabavian; Hossein Alipour (Hamadan University of Medical Sciences, 2022)
Background and Objective: In January 2020, the outbreak of the COVID-19 disease was declared an international health crisis by the World Health Organization (WHO). Nurses are mostly in close contact with patients during hospitalization. Since nursing students provide patient care alongside nurses, the discovery of nursing students' lived experiences of caring for COVID-19 patients is of paramount importance in the effective management of the disease. The present study aimed to assess nursing students' experiences of caring for patients diagnosed with COVID-19. Materials and Methods: This qualitative study was performed by the hermeneutic phenomenological method in 2021. Samples were selected from nursing students with experience of caring for Covid-19 patients in Mazandaran University of Medical Sciences. Data were collected through semi-structured and individual interviews and analyzed simultaneously and continuously by the Van Manen method. Results: Nursing students' lived experiences in caring for Covid-19 patients included three main categories and seven subcategories: 1) conflicting emotions (anxiety, mental involvement, and maturity), 2) psychosomatic problems (sleep disorders, skin problems, and neurological problems), and 3) self-awareness and empowerment (efforts made in patient care, striving for self-preservation). Conclusion: As evidenced by the results of the present study, nursing students experienced anxiety, stress, and mental preoccupation in caring for a patient with Covid-19. On the other hand, participants were satisfied and proud of being able to provide patient care during this period. In this regard, students gained experience in caring for themselves and patients strived to reduce stress and provide proper care. According to the findings of this study, the education system and university administrators can help reduce psychological stress and improve the quality of care in nursing students through holding web-based courses on stress management skills, training on the use of personal protective equipment, and observing health protocols.